If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 8 + -1x = 8 + 3x + -6 Reorder the terms: 8 + 3x + -1x = 8 + 3x + -6 Combine like terms: 3x + -1x = 2x 8 + 2x = 8 + 3x + -6 Reorder the terms: 8 + 2x = 8 + -6 + 3x Combine like terms: 8 + -6 = 2 8 + 2x = 2 + 3x Solving 8 + 2x = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 8 + 2x + -3x = 2 + 3x + -3x Combine like terms: 2x + -3x = -1x 8 + -1x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 8 + -1x = 2 + 0 8 + -1x = 2 Add '-8' to each side of the equation. 8 + -8 + -1x = 2 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = 2 + -8 -1x = 2 + -8 Combine like terms: 2 + -8 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 2y+2y-19y+35=0 | | 50.09+3.75x=800 | | 9x^2+12x=-9 | | 2.1+x=5.4 | | -3(4y-7)+2(3y+8)= | | (6x-4)+(4x+39)=180 | | 3x+4=17x+6 | | b-31b= | | x^2=(2x-7)(2x+13) | | -[5x-(3x+1)]=-6-[3(2x-4)-2x] | | (M-3)SQUARED(M-4)=0 | | 5Y^2-Y-12=0 | | 12(x+4)=14(x-2) | | 67+4x+15=90 | | X^2-Y^2-6X-4Y+4=0 | | -6a^6+4a^5-2a^4= | | -2-5cos(x)+6sin^2x=0 | | 2(X+X-7)=3(X+9+X+2+X-7) | | 5x+8x-20=0 | | -2+0.9+0.5(-2)=-2.1 | | (X)(-x)(-2x)= | | 3X^2-XY=0 | | (X)(2x)(y)= | | (5x)(2x)(x)= | | 6-2x=2(1x+3) | | X=5s | | 2(7-x)+5(x+1)=10(1+x)-9(x+1) | | 400=49.91x | | 9(2x+3)=18x+27 | | 5.70=0.05x+1.70 | | 14x+43-25x=229 | | y=0.05(27)+1.70 |